A novel fabrication technique for electrodes of PEM water electrolyzers - Buehler, M.; Klose, C.; Hegge, F.; Lickert, T.; Thiele, Simon (ECS Transactions, 2017)
In this work the improvement of material interfaces at electrodes for proton exchange membrane (PEM) water electrolyzers is addressed by a novel fabrication technique. In this approach the electrode and the membrane are directly deposited on the porous transport layers (PTLs), which serve as substrate for the electrodes. The aim is to stabilize and increase the oxygen and hydrogen evolution rate at high current densities leading to a reduction of the noble metal loading of the electrodes - and additionally to develop a cost effective novel fabrication technique applicable for the large scale industrial fabrication of electrodes for PEM water electrolyzers. The innovative manufacturing technique is described in this transaction, and current challenges regarding the coating of porous substrates in terms of parameter control, reliability and homogeneity are pointed out.
CRIS-Team Scopus Importer:2023-03-29